SISTEM KHILAFAH ISLAMIYAH DALAM PERSPEKTIF KETATANEGARAAN REPUBLIK INDONESIA - FATNI ERLINA (Jurnal Idea Hukum, 2019)
Khilafah Islamiyah can be interpreted as a government based on Islamic Shari'ah. The Islamic Khilafah is coveted by some Islamic groups as an effective way to hold power, and establishes it as a religious obligation. In a country with a majority of the population is Muslim, but uses a general constitution like Indonesia, the idea of the Islamic Caliphate is a special dilemma. Is it true that the practice of Indonesian constitution which has been going on in stark contrast to the values contained in the Islamic Khilafah, may have been partially accommodated, or even fully in line. Questions like this must be found as quickly as possible so that divisions can be avoided, in the midst of the increasingly rowdy debate on the pros and cons of the Caliphate.This study aims to analyze in depth the meaning of the Islamic Caliphate in the perspective of the constitutional system of the Republic of Indonesia. The research method used in this research is normative juridical. Focusing on the normative method, according to the discussion of the analysis, this method is called normative analysis. Comparative and hystorical approach are some of the approaches used.The results of this study conclude that: First, the basic values contained in the Islamic Caliphate movement are deliberation, justice, equality, brotherhood. Second, these values are indirectly reflected in Pancasila, obedience to leaders in the first principle, peace, recognition and protection of human rights in the second principle, deliberation on the fourth principle, justice, equality and free trial in the 5th precept. The conclusion of this study is that the values of the Islamic Khilafah can be contextualized in the practice of Indonesian constitution, such as the value of deliberation realized through an honest and fair electoral system. Islamic Sharia can be implemented through the enforcement of free and impartial law supremacy. The value of universal brotherhood is realized through international relations in a free and active political framework.